Analisa Kinerja Keuangan PT. Garuda Indonesia Periode 2012-2018 - Aswin Priyadi; Haris Maupa; Wahda Rasyid (Magister Management, Hasanuddin University, 2019)
Commercial aviation is a part of aviation industry which specializes in operating aircraft for passenger and cargo. PT Garuda Indonesia is a one flag carrier that has a worldwide reputation in aviation industry. This study analyzes the financial performance of the Indonesian aviation industry, with specific reference to the PT. Garuda Indonesia, Tbk for the period 2012-2018. This research uses descriptive type of research. The data required in this research is collected based on secondary data. The financial performance has been explored to support this study by analyzing the financial statements throughout 2012-2018. The data collected from the company’s prospectus, annual reports, and other sources to help the researcher to analyze the financial performance. The financial ratios which are used in this research are liquidity ratio, profitability ratio, and solvency ratio to determine the financial performance each year. Continue using DuPont Analysis, Compound Annual Growth Method (CAGR), and Optimal Capital Structure and SWOT Analysis. In the last 5 years PT. Garuda Indonesia experience once significant performance degradation in 2014, where the number of total operating expenses were higher than the total operating revenues. It was found that Garuda Indonesia currently suffering from high loss. A significant change is noticed in 2014 where net income fell up to 90%. In 2017 Garuda Indonesia also suffering too, which is the profit loss till US 213 million. This means the net income was not able to cover its expenses at that time. This event is occurred due to the rising domestic jet fuel price and depreciation of Indonesian local currency. The result of this analysis will be given to PT. Garuda Indonesia, Tbk. to improve the financial performance of the company and can be used as a reference for other airline to study financial performance of other airlines.